A Discrete-Time Controller for the Reduction of Commutation Torque Ripple in BLDCM Drives - Khudhair, Ihsan Obayes Khudhair; Turker, Turker (IEEE, 2016)
In this paper, a control strategy for the current loop of brushless DC motor (BLDCM) drives is proposed to reduce the commutation torque ripple. The proposed method consists of two different controllers based on dead-beat structure. Two different electrical model of BLDCM for conducting and commutation periods are considered by the controllers that are switched in conducting and commutation periods. In addition, a model based prediction is utilized to predict the beginning and ending of the commutation periods. Then, this information is used to modify the reference phase voltages in order to reduce commutation torque ripple. The characteristics of the proposed controller are evaluated by numerical simulations and satisfactory results are obtained.
Keywords: BRUSHLESS DC MOTOR; Computer Science; Engineering